DEFENSE MECHANISM OF BELLA SWAN REFLECTED IN CHRIS WEITZ'S NEW MOON MOVIE (2009): A PSYCHOANALYTIC APPROACH - ATMAJA , KURNIAWAN DWI (2011)
The major problem of this study is how the defense mechanism of the major character, Bella Swan, is reflected in Chris Weitz's New Moon movie. The objective of this study is to analyze the movie based on its structural elements, and based on psychoanalytic approach. The benefits of the study are to give some contributions to the larger body of knowledge particularly studies in Chris Weitz's New Moon movie. The study belongs to the qualitative study. The object of the study is Bella Swan's New Moon movie published in 2009 by Summit Entertainment. The primary data source is the main data obtained from all the images which form such like the scene of the movie itself and the texts which form such like words, phrases, and sentences in dialogues or monologues occurring in the movie related to the topic and the secondary data sources are the other data related to the analysis such as the author's biography and some reference books. The method of data collection is library research by note-taking for the texts and image-capturing for the images. The technique of data analysis used in this study is descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis, Bella is an American woman from middle class who is stubborn. She also has a private mind that all vampires can not read. Second, based on psychoanalytic analysis, Bella's life is directed by her ego. She uses ego defense to reduce her anxiety such as denial, displacement, reaction formation, rationalization, and undoing.